2019
DOI: 10.5433/1679-0359.2019v40n1p149
|View full text |Cite
|
Sign up to set email alerts
|

Viability of probiotic bacteria in tropical mango juice and the resistance of the strains to gastrointestinal conditions simulated in vitro

Abstract: This study evaluated the viability of Lactobacillus acidophilus La-05, Lactobacillus plantarum LP299v and Lactobacillus rhamnosus GG in tropical mango juice, the resistance of the strains to gastrointestinal conditions simulated in vitro and the microbiological, physicochemical and sensory characteristics of the products obtained. The viabilities of L. rhamnosus GG and L. plantarum LP299v were greater than 7.96 log CFU mL-1 and 7.74 log CFU mL-1, respectively, during the 28 days of storage at 8 °C. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There was a reduction in the cells of the microorganism after 35 days of storage of a fermented apple juice drink without sucrose, however, this reduction did not interfere with the viability of the product [26]. Other studies report a reduction in the viability of probiotic strains as a function of the storage time of the drink [28,25]. In this study, 14 days is the maximum time for which probiotic drinks can be stored under refrigeration.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…There was a reduction in the cells of the microorganism after 35 days of storage of a fermented apple juice drink without sucrose, however, this reduction did not interfere with the viability of the product [26]. Other studies report a reduction in the viability of probiotic strains as a function of the storage time of the drink [28,25]. In this study, 14 days is the maximum time for which probiotic drinks can be stored under refrigeration.…”
Section: Discussionmentioning
confidence: 65%
“…However, this value cannot be used as a parameter for a drink fermented by water kefir, since this microorganism can be grown in different culture media of non-dairy origin, and these have different physical-chemical characteristics from milk, which directly influences the value of that variable. The acidity of a drink is essential for acceptance by the consumer, being a fundamental criterion for consumption and acceptance of the product [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid bacteria grew and survived in mango juice, and this may be attributed to nutrients (carbohydrates, organic acids, vitamins, and minerals) in mango that are a source of energy for metabolism. Other studies have also demonstrated mango as a suitable medium for lactic acid bacteria growth [4][5][6][7]. After fermentation, the acidity of fermented mango juices increased, and this may be antagonistic to pathogenic microorganisms increasing juice shelf-life.…”
Section: Discussionmentioning
confidence: 97%
“…Mango juice is often fermented to wine using yeasts (Saccharomyces cerevisiae) [3] but not as a non-alcoholic fermented juice. The few studies that investigated the use of lactic acid bacteria (Lactobacilli) as starter cultures in mango juice [4][5][6][7] lack an in-depth consumer study of the sensory acceptability of fermented non-alcoholic mango juices. Jin et al [4] suggested consumer sensory evaluation as the next step to the formulation of non-alcoholic fermented mango juices.…”
Section: Introductionmentioning
confidence: 99%